New Targets of Neuroprotection in Ischemic Stroke - Marco Bacigaluppi; Dirk M. Hermann (The Scientific World Journal)
Ischemic stroke represents one of the most challenging diseases in translational neurology. Despite the considerable efforts made to develop efficacious therapies that prevent damage once a stroke has occurred, there are still no established treatments for humans. The only available treatment is intravenous or intra-arterial thrombolysis that is limited to the very first hours after the stroke. Starting with recent findings about the pathophysiology of stroke and presenting an overview on current experimental models of this clinically highly relevant neurological disease, this paper will provide an overview on existing and emerging treatment concepts in ischemic stroke. Thus, our review will present an analysis of established and innovative strategies of neuroprotection and neurorestoration, highlighting both pharmacological and cell-based treatment concepts. In the last section of our paper, we will examine more closely how experimental data are presently translated to humans, with particular emphasis on the bioaccumulation and efficacy of drugs. From this point of view, we will try to develop ideas of how causative treatments in ischemic stroke may be established.